Form Of Communication By Dance (Case Study: Young Generation In Hatu Village-Moluccas) - Trientje Marlein Tamtelahitu (INJECT (Interdisciplinary Journal of Communication), 2020)
The purpose of this research is that the young generation in the Hatu village know and love the culture of the local area, regional culture of Mollucas, traditional dance arts Cakalele, Orlapei, Maku-Maku and Saureka-Reka. The benefits of research is to add the treasures or knowledge of the younger generation to traditional arts so that it can preserve the culture of the region. The research method used is a descriptive approach, which is a direct approach to the intended object. In the location of the study took a number of data needed to then be processed into detailed information. Retrieval of this data with interviews and surveys. The results achieved were reintroducing regional dances to the younger generation by doing a combination of these dances. Thus, raises concern for the regional culture.